(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The objective of this proposed paper is to re-read the novel In the Kitchen (2009) by theBangladeshi-British novelist Monica Ali with a view to pointing out the role and significance of ‗place‘ and‗displacement‘ in the marginalization of individuals as well as communities in a globalized situation.Attempts will be made to assess Monica Ali‘s representation of ‗Imperial Hotel, London‘ as a fictive locusthat at once employs and exploits the veritable ‗ends of the earth‘-a set of foreigners and outsiderswhose marginality is, by and large, locational for social ills like human trafficking, ethnic discrimination,and economic disparity may, and do, place some at a disadvantage and some others in control. I shallalso seek to show how displaced characters and misplaced ambitions complicate the human situation tosuch an extent that organized crime and bureaucratic incompetence hold sway over the innocent and theguilty alike.